Motor dysfunction in cerebellar Purkinje cell-specific vesicular GABA transporter knockout mice - Kayakabe, Mikiko; Kakizaki, Toshikazu; Kaneko, Ryosuke; Sasaki, Atsushi; Nakazato, Yoichi; Shibasaki, Koji; Ishizaki, Yasuki; Saito, Hiromitsu; Suzuki, Noboru; Yanagawa, Yuchio (Frontiers in Cellular Neuroscience, 2014)
γ-Aminobutyric acid (GABA) is a major inhibitory neurotransmitter in the adult mammalian central nervous system and plays modulatory roles in neural development. The vesicular GABA transporter (VGAT) is an essential molecule for GABAergic neurotransmission due to its role in vesicular GABA release. Cerebellar Purkinje cells (PCs) are GABAergic projection neurons that are indispensable for cerebellar function. To elucidate the significance of VGAT in cerebellar PCs, we generated and characterized PC-specific VGAT knockout (L7-VGAT) mice. VGAT mRNAs and proteins were specifically absent in the 40-week-old L7-VGAT PCs. The morphological charactereistics, such as lamination and foliation of the cerebellar cortex, of the L7-VGAT mice were similar to those of the control littermate mice. Moreover, the protein expression levels and patterns of pre- (calbindin and parvalbumin) and postsynaptic (GABA-A receptor α1 subunit (GABAARα1) and gephyrin) molecules between the L7-VGAT and control mice were similar in the deep cerebellar nuclei that receive PC projections. However, the L7-VGAT mice performed poorly in the accelerating rotarod test and displayed ataxic gait in the footprint test. The L7-VGAT mice also exhibited severer ataxia as VGAT deficits progressed. These results suggest that VGAT in cerebellar Purkinje cells is not essential for the rough maintenance of cerebellar structure, but does play an important role in motor coordination. The L7-VGAT mice are a novel model of ataxia without PC degeneration, and would also be useful for studying the role of Purkinje cells in cognition and emotion.